Terrorism Research Centres: 100 Institutes, Programs and Organisations in the Field of Terrorism, Counter-Terrorism, Radicalisation and Asymmetric Warfare Studies - Benjamin Freedman (Perspectives on Terrorism, 2010)
Who is doing research – academic and otherwise – on terrorism? The field of terrorism research is broad and ever-expanding. Governments sponsor intelligence-driven analytical research agencies. Commercial intelligence firms like Jane’s, sell their research to corporate and governmental clients. There are think tanks likeRAND, which work closely with government agencies. An increasing number of universities house terrorism research centres, the oldest one being the Centre for the Study of Terrorism and Political Violence at the University of St. Andrews. Then there are virtual networks, such as the Terrorism Research Initiative (TRI), that try to create synergies between a wide array of researchers and topics.